Cross‐cultural differences in types and beliefs about treatment in women with temporomandibular disorder pain. (16th July 2018) - Al‐Harthy, Mohammad; List, Thomas; Ohrbach, Richard; Michelotti, Ambra
Summary: Objectives: Women with temporomandibular disorder (TMD) pain from three cultures were assessed for type of treatment received and core illness beliefs. Methods: In a clinical setting, 122 women patients with chronic TMD pain (39 Saudis, 41 Swedes and 42 Italians) were evaluated for patient characteristics, type of practitioner, type of treatment received and beliefs about TMD prior to consultation in TMD specialist centres. Measures included a survey of treatments received and a belief scale regarding contributing, aggravating and treatment‐relevant factors related to the pain. All questionnaires were translated from English and culturally adapted. Comparisons among cultural groups were performed using a linear regression model for continuous variables and logistic regression model for dichotomous variables. A P ‐value < 0.05 was considered statistically significant. Results: The study found no significant associations between cultures and the type of practitioners consulted previously. Treatments differed among cultures: Swedes most commonly received behavioural therapy, acupuncture and an occlusal appliance; Saudis most commonly received Islamic medicine; and Italians most commonly received an antidepressant. Swedes were significantly more likely than Saudis and Italians to believe that TMD pain treatment should address behavioural factors. Conclusions: Among Saudi, Italian and Swedish women with chronic TMD pain, culture does not influence the type of practitioner consulted before visiting a TMD specialist or their beliefs about contributing and aggravating factors for their pain. However, treatment types and beliefs concerning mechanisms underlying the pain differed cross‐culturally, with local availability or larger cultural beliefs also probably influencing the types of treatments that TMD patients pursue.